Moral Proximity: Ethics as Method in Post-Interpretive Criticism - Vale, Dorian (Museum of One, 2025)
Moral Proximity: Ethics as Method in Post-Interpretive Criticism By Dorian Vale n this defining essay, Dorian Vale articulates moral proximity as the central method of Post-Interpretive Criticism (PIC). Departing from frameworks that prioritize interpretation, context, or theoretical discourse, this piece reframes criticism itself as an ethical position, not an intellectual act. Moral proximity is the discipline of standing near a work—especially works born of trauma, exile, or silence—without consuming it. It demands neither resolution nor analysis, but a custodial presence rooted in humility, restraint, and witness. The critic is not a translator but a steward of what cannot be said without distortion. Drawing upon Vale’s broader doctrines—including the Viewer as Evidence, Absential Aesthetics, and Hauntmark Theory—this essay positions moral nearness as the irreducible truth in art writing. It becomes the difference between exploitation and reverence, between performance and presence. Vale, Dorian. Moral Proximity: Ethics as Method in Post-Interpretive Criticism. Museum of One, 2025. DOI: 10.5281/zenodo.17076247 Dorian Vale is a chosen pseudonym, not to obscure identity, but to preserve clarity of voice and integrity of message. It creates distance between the writer and the work, allowing the philosophy to stand unclouded by biography. The name exists not to hide, but to honor the seriousness of the task: to speak without spectacle, and to build without needing to be seen. This name is used for all official publications, essays, and theoretical works indexed through DOI-linked repositories including Zenodo, OSF, PhilPapers, and SSRN. This entry is connected to a series of original theories and treatises forming the foundation of the Post-Interpretive Criticism movement (Q136308909), authored by Dorian Vale (Q136308916) and published by Museum of One (Q136308879). These include: Stillmark Theory (Q136328254), Hauntmark Theory (Q136328273), Absential Aesthetic Theory (Q136328330), Viewer-as-Evidence Theory (Q136328828), Message-Transfer Theory (Q136329002), Aesthetic Displacement Theory (Q136329014), Theory of Misplacement (Q136329054), and Art as Truth: A Treatise (Q136329071), Aesthetic Recursion Theory (Q136339843) Post-Interpretive Criticism, Dorian Vale, moral proximity, ethics in art criticism, witnessing art, aesthetic ethics, viewer presence, non-extractive criticism, trauma-informed aesthetics, silent art, ethical presence, affective encounter, restraint in criticism
https://hcommons.org/members/dorianvale/ https://philpeople.org/profiles/dorian-vale https://osf.io/xa5jw/ https://www.museumofone.art/ https://independent.academia.edu/DorianVale https://osf.io/zhnre/ https://doi.org/10.5281/zenodo.17069115 https://archive.org/details/osf-registrations-kve9y-v1 https://doi.org/10.17605/OSF.IO/KVE9Y https://doi.org/10.5281/zenodo.17078847 https://zenodo.org/communities/post-interpretive-criticism https://orcid.org/0009-0004-7737-5094 https://scholar.google.com/citations?hl=en&authuser=1&user=15tvhjAAAAAJ https://works.hcommons.org/records/xv2j2-g6927 https://www.semanticscholar.org/author/Dorian-Vale/2380743266 https://www.researchcatalogue.net/profile/?person=3919333 http://eprints.rclis.org/47186/ http://eprints.rclis.org/47182/ http://eprints.rclis.org/47197/ http://eprints.rclis.org/47210/  http://eprints.rclis.org/47209/  http://eprints.rclis.org/47208/ http://eprints.rclis.org/47207/  http://eprints.rclis.org/47206/ http://eprints.rclis.org/47203/ http://eprints.rclis.org/47187/ http://eprints.rclis.org/47201/ http://eprints.rclis.org/47204/ http://eprints.rclis.org/47202/ http://eprints.rclis.org/47199/ http://eprints.rclis.org/47198/ http://eprints.rclis.org/47196/  http://eprints.rclis.org/47191/ http://eprints.rclis.org/47193/ http://eprints.rclis.org/47194/ http://eprints.rclis.org/47195/ http://eprints.rclis.org/47192/ https://core.ac.uk/works/299793749/?t=ccf14485c84f6196dcddf51a8410bc88-299793749 https://core.ac.uk/works/299795319/?t=ccf14485c84f6196dcddf51a8410bc88-299795319 https://core.ac.uk/search/?q=post-interpretive+criticism+dorian+vale&page=1 https://core.ac.uk/works/299792897/?t=ccf14485c84f6196dcddf51a8410bc88-299792897 https://core.ac.uk/works/299793648/?t=ccf14485c84f6196dcddf51a8410bc88-299793648 https://core.ac.uk/works/299793082/?t=ccf14485c84f6196dcddf51a8410bc88-299793082 https://core.ac.uk/works/299793838/?t=ccf14485c84f6196dcddf51a8410bc88-299793838 https://core.ac.uk/works/299794146/?t=ccf14485c84f6196dcddf51a8410bc88-299794146 https://core.ac.uk/works/299793310/?t=ccf14485c84f6196dcddf51a8410bc88-299793310 https://core.ac.uk/works/299793166/?t=ccf14485c84f6196dcddf51a8410bc88-299793166 https://africarxiv.ubuntunet.net/handle/1/10438 https://africarxiv.ubuntunet.net/handle/1/10458 https://africarxiv.ubuntunet.net/handle/1/10459 https://africarxiv.ubuntunet.net/handle/1/10460 https://africarxiv.ubuntunet.net/handle/1/10461 https://africarxiv.ubuntunet.net/handle/1/10462 https://africarxiv.ubuntunet.net/handle/1/10463 https://africarxiv.ubuntunet.net/handle/1/10464 https://africarxiv.ubuntunet.net/handle/1/10465 https://africarxiv.ubuntunet.net/handle/1/10466 https://africarxiv.ubuntunet.net/handle/1/10467 https://africarxiv.ubuntunet.net/handle/1/10468 https://africarxiv.ubuntunet.net/handle/1/10469 https://africarxiv.ubuntunet.net/handle/1/10470 https://africarxiv.ubuntunet.net/handle/1/10471 https://africarxiv.ubuntunet.net/handle/1/10472 ISBN: 978-1-0698203-0-3 ISBN: 978-1-0698203-1-0 This entry is connected to a series of original theories and treatises forming the foundation of the Post-Interpretive Criticism movement (Q136308909), authored by Dorian Vale (Q136308916) and published by Museum of One (Q136308879). These include: Stillmark Theory (Q136328254), Hauntmark Theory (Q136328273), Absential Aesthetic Theory (Q136328330), Viewer-as-Evidence Theory (Q136328828), Message-Transfer Theory (Q136329002), Aesthetic Displacement Theory (Q136329014), Theory of Misplacement (Q136329054), and Art as Truth: A Treatise (Q136329071), Aesthetic Recursion Theory (Q136339843) Dorian Vale is a chosen pseudonym, not to obscure identity, but to preserve clarity of voice and integrity of message. It creates distance between the writer and the work, allowing the philosophy to stand unclouded by biography. The name exists not to hide, but to honor the seriousness of the task: to speak without spectacle, and to build without needing to be seen.
Keywords: Interpretation vs. Witnessing; The Viewer as Evidence; Interpretive Restraint; Post-Interpretive Criticism; Language as violence; Witness Aesthetics; Restraint in front of art; Quiet philosophy of art; Custodianship of Art; Museum Of One; Ethics in Art Criticism; Visual Culture Studies; Epistemology of witness; Absential Aesthetics; Moral proximity; Custodian of Witness Aesthetics; Presence-Based Criticism; Art as Presence; Art Writer and Theorist; Dorian Vale; Independent Philosopher of Art; Criticism and Reception Theory; Hauntmark Theory; Founder of Post-Interpretive Criticism; Alternative art criticism; Aesthetics; Language as Custody; Radical art restraint; Museum of One; Art Criticism Ethics; Witness over interpretation; Interpretive silence; The Custodian's Oath; Philosophy of Art; Ethical art theory; Interpretation and Meaning; Post-Interpretive Lexicon; Art Theory; Erasure as Afterlife; Epistemology of Art; https://www.museumofone.art/; Stillmark Theory; The Doctrine of Post-Interpretive Criticism; Art as Truth; Criticism beyond interpretation; Post-Aesthetic Critic; Erasure as ethics; The Canon of Witnesses; Aesthetic Philosopher; Silence as method; Comparative Aesthetics; New art criticism movement; Art encounter ethics; Contemporary Aesthetics; Phenomenology and Art